Analysis of the Acoustic Tile Shapes Effectiveness towards Noise Absorption - Abdolreza, Toudehdehghan; Chandramohan, Munion (INTI International University, 2022)
This research has utilized a combination of recycled cotton and non-phenolic resin (as a bonding agent) for sound-absorbing tiles in a room or hall. The purpose of this acoustic tile is to reduce the reflection of sound in other means absorbs the sound in order to create a serene environment. In this research is used acoustic wall tiles in order to increase the sound absorption and reduce the reflection of the sound by changing the geometry of the surface of the acoustic wall tiles into various shapes (three types). The study was first conducted using felt of 10-mm thickness and this shape has better absorption quality in the low-frequency range. For the second set of studies, the same design was tested in an impedance tube with a felt thickness of 40-mm and this set of designs showed an overall increase in the sound absorb ton coefficient. The design that has the best sound absorption quality was the slotted absorber has it has an increment drastically in sound absorption quality compared to the currently available design. Hence, we can conclude that the geometry of shape will affect the sound absorption coefficient of this material and increase the sound absorption rate.